2009
DOI: 10.1107/s1600536809010496
|View full text |Cite
|
Sign up to set email alerts
|

(E)-1-(4-Bromophenyl)-3-(2,4,6-trimethoxyphenyl)prop-2-en-1-one

Abstract: The mol­ecule of the title chalcone derivative, C18H17BrO4, is twisted, the dihedral angle between the 4-bromo­phenyl and 2,4,6-trimethoxy­phenyl rings being 39.17 (6)°. The three meth­oxy groups are oriented in two different conformations whereby two meth­oxy groups are coplanar, whereas the third is twisted with respect to the attached benzene ring [C—O—C—C torsion angles of −2.84 (18), −2.80 (18) and −9.31 (18)°]. Weak intra­molecular C—H⋯O inter­actions generate two S(5) and one S(6) ring motifs. In the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 12 publications
6
25
0
Order By: Relevance
“…The carbothioamide is slightly twisted from the pyrazole ring as indicated by the torsions angles N4-C18-N2-N1 = 5.51 (14)° and S1-C18-N2-N1 = -172.28 (7)°. The bond distances agree with the literature values (Allen et al, 1987) and are comparable to those observed in related structures (Chantrapromma et al, 2009;Suwunwong et al, 2009).…”
Section: Data Collectionsupporting
confidence: 90%
See 1 more Smart Citation
“…The carbothioamide is slightly twisted from the pyrazole ring as indicated by the torsions angles N4-C18-N2-N1 = 5.51 (14)° and S1-C18-N2-N1 = -172.28 (7)°. The bond distances agree with the literature values (Allen et al, 1987) and are comparable to those observed in related structures (Chantrapromma et al, 2009;Suwunwong et al, 2009).…”
Section: Data Collectionsupporting
confidence: 90%
“…For background to chalcone synthesis and the biological activity of pyrazole derivatives, see: Bekhit et al (2008); Ono et al (2007); Cottineau et al (2002); Gadakh et al (2010); Hall et al (2008); Hoepping et al (2007); Mikhaylichenko et al (2009); Park et al (2005) Souza et al (2002); Xie et al (2008). For related structures, see; Chantrapromma et al (2009); Suwunwong et al (2009). For the stability of the temperature controller used in the data collection, see Cosier & Glazer (1986).…”
Section: Related Literaturementioning
confidence: 99%
“…In the molecule, a weak intramolecular C7-H7A•••O4 interaction (Table 1) generates an S(6) ring motif (Bernstein et al, 1995). The bond distances are of normal values (Allen et al, 1987) and comparable with related structures (Chantrapromma et al, 2009;Fun et al, 2010;.…”
Section: Data Collectionmentioning
confidence: 70%
“…For hydrogenbond motifs, see: Bernstein et al (1995). For related structures, see: Chantrapromma et al (2009); Fun et al (2010Fun et al ( , 2011. For background to and applications of chalcones and heteroaryl chalcones, see: Bandgar et al (2010); Gacche et al (2008); Go et al (2005); Isomoto et al (2005); Jung et al (2008); Suwunwong et al (2011); Tewtrakul et al (2003).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation